1999
DOI: 10.1023/a:1020610424625
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Cereals, Plants and Tubers Through Protein Composition

Abstract: Wild and cultivated maize, sorghum, rice, amaranth, soybean, and cassava were screened for variability in seed storage proteins. Total seed proteins, albumin (Alb-1 and Alb-2), globulin, alcohol-soluble (A1 and A2), and glutelin (G1 and G2) fractions were investigated by means of sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The comparison was done by the obtained protein patterns and their relative amounts. Using quantitative analysis of the protein composition and the electrophoretic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…While A. hybridum 1004 and hypochondriacus v .1023 had main bands of Alb-2, most bands were observed in globulins for A. cruentus R104 ( Figure ). Soybean showed a major globulin band at 30 kDa and a low molecular weight band confirming findings of ( , ). Differences were observed between albumins (Alb-1 and Alb-2) and globulins of buckwheat and rice.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…While A. hybridum 1004 and hypochondriacus v .1023 had main bands of Alb-2, most bands were observed in globulins for A. cruentus R104 ( Figure ). Soybean showed a major globulin band at 30 kDa and a low molecular weight band confirming findings of ( , ). Differences were observed between albumins (Alb-1 and Alb-2) and globulins of buckwheat and rice.…”
Section: Resultssupporting
confidence: 86%
“…Our results are not in full correspondence with others, who have shown that the amount of Alb-2 comprised about 30% of the total albumin and globulin content. Little or no measurable protein corresponding to the amaranth Alb-2 was extracted from seeds of buckwheat and quinoa ( , ).…”
Section: Resultsmentioning
confidence: 99%
“…Mezi nejmodernější varianty patří např. kapilární zónová elektroforéza s UV detekcí [28], chromatografie na reverzní fázi s fluorometrickou detekcí derivátů aminokyselin [29], kapilární zónová elektroforéza s elektrochemickou detekcí [30] a s následnou bezkontaktní vodivostní detekcí (contactless conductivity detection) [31], iontovýměnná chromatografie a elektroforéza s FT-IR [32,33], plynová chromatografie s chirální stacionární fází ke stanovení enantiomerů aminokyselin [34], insitu fotometrické fluorimetrické stanovení aminokyseliny tyrosinu [35], isokratické stanovení nederivatizovaných aminokyselin s ampérometrickou detekcí [36]. Dále sem patří metoda ke stanovení peptidů a aminokyselin s fluorescenčním činidlem 2-(9-karbazol)-Et chloroformat (CEOC) pomocí HPLC na reverzní fázi a hmotnostní spektrometrie [37], nová HPLC metoda k simultánnímu stanovení aminokyselin a aminů jako o-ftaldialdehyd derivátů [38], stanovení biogenních aminů metodou Heavy Atom Induced Phosphorescence (HAI-RTP) […”
Section: Přehled Metod Stanovení Aminokyselinunclassified